ChemInform Abstract: A Photochemical Strategy for Lignin Degradation at Room Temperature. Issue 34 (26th August 2014) - Nguyen, John D.; Matsuura, Bryan S.; Stephenson, Corey R. J.
Abstract A proof‐of‐principle approach to address the lignin degradation is presented.